Europe in the Trumpworld: EU trade and security under the new US executive - Fredrik Erixon; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2016)
The election of Trump into the Oval Office is much of a non-event for EU trade-policy detail, possibly even the TTIP: they have been deteriorating for years. Europe and the global trading system can survive new trade frictions and creeping protectionism, but a Trump that wants to go radical will make everyone miserable.
Keywords: 330; Außenwirtschaftspolitik; Handelspräferenzen; TTIP-Staaten; EU-Staaten; USA